Assessment of high enthalpy geothermal resources and promising areas of Chile. (January 2016) - Aravena, Diego; Muñoz, Mauricio; Morata, Diego; Lahsen, Alfredo; Parada, Miguel Ángel; Dobson, Patrick
Abstract : Highlights: We ranked geothermal prospects into measured, Indicated and Inferred resources. We assess a comparative power potential in high-enthalpy geothermal areas. Total Indicated and Inferred resource reaches 659 ± 439 MWe divided among 9 areas. Data from eight additional prospects suggest they are highly favorable targets. 57 geothermal areas are proposed as likely future development targets. Abstract: This work aims to assess geothermal power potential in identified high enthalpy geothermal areas in the Chilean Andes, based on reservoir temperature and volume. In addition, we present a set of highly favorable geothermal areas, but without enough data in order to quantify the resource. Information regarding geothermal systems was gathered and ranked to assess Indicated or Inferred resources, depending on the degree of confidence that a resource may exist as indicated by the geoscientific information available to review. Resources were estimated through the USGS Heat in Place method. A Monte Carlo approach is used to quantify variability in boundary conditions. Estimates of total Indicated resource are confined to 3 geothermal systems; Apacheta, El Tatio and Tolhuaca, yielding a total value of 228 ± 154 MWe. The estimates of the total Inferred resources for Chile include 6 geothermal systems and yield a total value of 431 ± 321 MWe. Standard deviation reflects the high variability of reservoir specific parameters for each system. A set of 65 favorable geothermal areas are proposed as the most likely future development targets. Eight of them have initial exploration results that suggest they are highly favorable targets as potential geothermal resources.